Emotional Lability in Children and Adolescents Affected by Tourette Syndrome - Gulisano, Mariangela; Pellico, Alessandra; Palermo, Filippo; Curatolo, Paolo; Rizzo, Renata (Journal of Pediatric Neurology, 2015)
Ninety-two patients with Tourette syndrome (TS) were studied to investigate the occurrence of emotional lability (EL) in TS, its relationship to comorbid conditions, and the risk of developing bipolar disorder (BD). Patients were divided in three clinical subgroups, according with child behavior checklist anxious/depressed, attention and aggressive scales: group (G) 1: score >210 (risk of development BD), G2: score >180 but < 210 (patients with EL), G3: score <180 (normal). In G1, 9.3% of patients with no “pure TS” were observed (TS + ADHD [attention deficit hyperactivity disorder], 23%); TS + OCD [obsessive compulsive disorder], 67%; TS + ADHD + OCD, 10%). In G2, 44.3% of patients with “pure TS” as “TS + comorbidity” were represented. In G3, 46% of patients with “TS + comorbidity” were observed, while 64% of patients with “pure TS” were represented. Our findings suggested that EL is a core feature in TS, related to mood and anxiety disorders. Comorbid conditions such as ADHD and OCD were important factors responsible of TS malfunctioning causing anxiety and depressive symptoms and increase the risk of developing BD.
Keywords: Tourette syndrome; emotional lability; bipolar disorder; ADHD; obsessive compulsive disorder